(untitled) (BIBECHANA, 2016)
Basic concepts of the Quantum Behavior of atoms and molecules, modified concepts of General Relativity and the Doppler Factor were applied to a reflection associated with solar sailing and laser-driven light sailing, which provides the motion in the sailing due to energy and momentum transfer of the photons to the sail. The result of this application is the energy and momentum being conserved, for the first time, from the perspective of the reflector and the source. The magnitude and the direction of the reflector, after a reflection, are not consistent with current beliefs of the reflection of a photon, which is a consequence of the conservation proposed in this paper. That is, the energy and momentum transfer are far smaller than what is currently believed. An experimental test to verify the actual energy and momentum transfer from a photon to a reflector is also proposed. BIBECHANA 14 (2017) 9-16